Assessment of Groundwater Quality at Yuncheng Basin: Denotation for the Water Management in China. Issue 3 (26th November 2018) - Li, Chengcheng; Gao, Xubo
Abstract: Dramatic decreases in groundwater quality have raised widespread concerns about water supplies and ecological crises in China. In this study, hydrochemistry, stable isotopes, and graphical and multivariate statistical methods are integrated to identify hydrogeochemical processes controlling groundwater quality in the Yuncheng Basin, China. Our results show that groundwater with 21 variables (pH, temperature‐T, total dissolved solid, major‐trace elements, and stable isotopes) is chemically classified into three distinct clusters: fresh water [C1], brackish‐saline water [C2], and saline water [C3]. Groundwater salinization is identified as the prime process in controlling groundwater quality for shallow groundwater and deep groundwater in the lowland areas. Large‐scale As, F, or B contaminations found in groundwater are closely related to groundwater salinization, agricultural activity, and the exploration of geothermal water in the area. With respect to the risk of contamination, groundwater in the basin is spatially divided into the following: shallow groundwater with a high risk located in the north side of the Salt Lake, shallow groundwater with a moderate risk, and deep groundwater with a low to moderate risk. Nationally, the increasing demand on groundwater is threatened by a range of environmental and health pressures, including salinization and contaminations of nitrate, As, F, or B. Our study indicates that natural water‐rock interactions and hydrogeological conditions are significant factors controlling these contaminations. Systematic management and regulation of existing groundwater resources are required to prevent further deterioration of groundwater resources. Policies should be made and implemented to ensure "green" exploitation of geothermal water. Abstract : Article impact statement : The article assesses groundwater quality and denotes groundwater management and regulation in the northern China.